Geodetic and hydrological research around Bulgarian Antarctic Base on Livingston Island, Antarctica - Alexandrov, B.; Tzanovsky, Yu. (Ukrainian Antarctic Journal, 2012)
This report displays the obstacles and specialties in doing geodetic and hydrographic works in the severe polar conditions of Antarctica, near Bulgarian Antarctic base on Livingston Island, South Shetland Islands. Surveying of the ice free rock passages by means of classical geodetic technology was made. The first hydrographical survey of a part of the South Bay, near Bulgarian base was made too and displays the specialties in hydrographical works in polar conditions. For the implementation of the set goals, GPS, hydroacoustic and classical geodetic equipment were used. We represent results from a digital modeling of the relief of South Bay (next to BAB) and surveyed territory on Livingston Island. A geographic information system is used.